Analysis of Slope Stability in Unsaturated Expansive Soil: A Case Study - Yang, Rong; Xiao, Peiwei; Qi, Shunchao (Frontiers in Earth Science, 2019)
To get a better understanding of failure mechanism of expansive soil slope under the rainfall condition, a field study conducted in Henan Province, China, is analyzed using a comprehensive numerical procedure that involves the seepage analysis based on finite element analysis, followed by Factor of Safety (FS) calculation based on Limit Equilibrium Method. Several hydraulic properties functions; including the unimodal SWCC and bimodal SWCC with the associated permeability functions are used to consider effects of cracks on the hydraulic properties of the shallow layer. The results suggest that the bimodal hydraulic properties can better represent the hydraulic behavior of cracked expansive soils, and result a close match between the predicted and measured variations of positive and negative pore water pressure over time. The calculated FSs illustrate the importance of selecting shear strength parameters under lower confining pressure obtained from laboratory tests in stability analysis of expansive soil surficial layer.